174k views
21 votes
Helpppppppppppppp pleaseeeeeeeee

Helpppppppppppppp pleaseeeeeeeee-example-1

1 Answer

9 votes

First, lets put this into slope intercept form

3x + 2y = -6

2y = -3x - 6

y = -3/2x - 3

The y intercept is (0, -3)

To find the x intercept we set the new equation to zero and solve

0 = -3/2x - 3

+3 +3

(2)3 = -3/2x(2)

6 = -3x

6/-3 = -3x/-3

-2 = x

The x intercept is (-2,0)

Therefore, your intercepts are:

y-int. = (0,-3)

x-int. = (-2,0)

Hope this helps! =D

User Hogan
by
5.2k points